2005
DOI: 10.1097/01.gme.0000185486.55758.5b
|View full text |Cite
|
Sign up to set email alerts
|

Dried plum reverses bone loss in an osteopenic rat model of osteoporosis

Abstract: Objective: We previously reported the efficacy of dried plum (Prunus domestica L.) in preventing ovariectomy-induced bone loss in a rat model of osteoporosis and improving bone biomarkers in postmenopausal women. The present study evaluated whether dried plum was able to restore bone mass in osteopenic ovariectomized rats.Design: Ninety-day-old Sprague-Dawley rats were either sham-operated (Sham; one group) or ovariectomized (Ovx; five groups) and were fed a standard diet for 40 days to establish bone loss and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 36 publications
(35 reference statements)
3
52
0
1
Order By: Relevance
“…The results from this in vitro experiment by Bu et al (2008) has also been confirmed in animal studies (Deyhim et al, 2005;Franklin et al, 2006;Bu et al, 2007;Smith et al, 2014a). Among these, the study by Smith et al (2014a) is slightly different in that unlike the other studies that studied longer term effects of dried plum on systemic biochemical markers of bone metabolism and alteration in gene expression as the main outcome measure, their main objective was to understand the mechanism of action by which dried plum altered bone metabolism.…”
Section: Bone Healthsupporting
confidence: 57%
See 1 more Smart Citation
“…The results from this in vitro experiment by Bu et al (2008) has also been confirmed in animal studies (Deyhim et al, 2005;Franklin et al, 2006;Bu et al, 2007;Smith et al, 2014a). Among these, the study by Smith et al (2014a) is slightly different in that unlike the other studies that studied longer term effects of dried plum on systemic biochemical markers of bone metabolism and alteration in gene expression as the main outcome measure, their main objective was to understand the mechanism of action by which dried plum altered bone metabolism.…”
Section: Bone Healthsupporting
confidence: 57%
“…Restoration of bone mineral density by two higher doses and bone turnover suppression (Deyhim et al, 2005) USA Dried plum (P.…”
Section: Domestica)mentioning
confidence: 99%
“…Prunes improve the liver function (Ahmed et al, 2010b), bone health (Hooshmand and Arjmandi, 2009. ) and increase bone mass, prevents osteoporosis (Deyhim et al, 2005;Bu et al, 2008), enhances the resistance to fungal infection (El-Kereamy et al, 2011), is anticancerous (Fujii et al, 2006) and anti hypercholestremia (Tinker et al, 1991).…”
Section: In Sarpagandha (Rauvolfia Serpentina)mentioning
confidence: 99%
“…OVX_25% dried plum also increased lumbar bone density significantly. Interestingly, dried plum fed in varying amounts improved trabecular microarchitectural properties, including bone volume and connectivity, in comparison with OVX after bone loss occurred (64).…”
Section: Hormone Deficiency and Osteoporosismentioning
confidence: 99%